Drought tolerance of two perennial ryegrass cultivars with and without AR37 endophyte. Issue 2 (3rd April 2017) - He, L.; Hatier, J.-H.B.; Matthew, C.
ABSTRACT: The objectives of this research were to investigate Lolium perenne L. responses to water deficit, compare drought tolerance of two cultivars derived from different germplasm and the role of endophyte in drought tolerance of the host cultivar. Plants of cultivars Ceres One50 and Grasslands Commando with and without AR37 endophyte were kept irrigated or unirrigated for two weeks and then rehydrated for one month in a glasshouse. A positive correlation between the extent of osmotic adjustment (OA) and leaf dry matter regrowth indicated that OA was correlated with the plant regrowth during recovery. For One50, the reduction in leaf elongation rate was less and the increase in proline was greater in response to drought, compared to Commando. From this observation, it was inferred One50 has enhanced capacity to continue growth, and had greater intra-cellular protection than Commando. Endophyte status did not affect plant responses to drought in this experiment.